Pengaruh corporate governance dan variabel keuangan terhadap nilai perusahaan - DEWI AGUSTINA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to determine and examine corporate governance (board of commissioner, independent commissioner, institutional ownership, managerial ownership and audit committee) and financial variabel measured by financial ratio such as leverage, activity, profitabilityand liquidity in affecting firm value in non financial companies listed in Indonesia Stock Exchange. This research used 91 listed non financial companies in Indonesia Stock Exchange, selected using purposive sampling method in period 2013 to 2015. The analysis was performed using multiple linear regressions analysis method to determine the model of research. The research results show that the board of commissioner, managerial ownership, leverage and profitability had influence towards firm value whereas, the independent commissioner institutional ownership, audit committee, activity and liquidity had no influence towards firm value.